2015
DOI: 10.3390/jcm4091668
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Potential of microRNA-7 in Cancer

Abstract: microRNAs (miRNAs) are a family of short, non-coding RNA molecules that drive a complex network of post-transcriptional gene regulation by enhancing target mRNA decay and/or inhibiting protein synthesis from mRNA transcripts. They regulate genes involved in key aspects of normal cell growth, development and the maintenance of body homeostasis and have been closely linked to the development and progression of human disease, in particular cancer. Over recent years there has been much interest regarding their pot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
28
0
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 98 publications
(159 reference statements)
4
28
0
1
Order By: Relevance
“…Extensive roles of miR-7 in regulating cancer cell initiation, proliferation, migration, invasion, survival and death by targeting a number of oncogenic signaling pathways have been reported [27, 28]. Partially consist with the role of miR-7 in down-regulating FAK and inhibiting the ERK/MAPK signaling pathway, miR-7 overexpression is associated with suppressed proliferation, cell migration and tumorigenicity, and induced cell apoptosis in NSCLC cells [29].…”
Section: Discussionmentioning
confidence: 99%
“…Extensive roles of miR-7 in regulating cancer cell initiation, proliferation, migration, invasion, survival and death by targeting a number of oncogenic signaling pathways have been reported [27, 28]. Partially consist with the role of miR-7 in down-regulating FAK and inhibiting the ERK/MAPK signaling pathway, miR-7 overexpression is associated with suppressed proliferation, cell migration and tumorigenicity, and induced cell apoptosis in NSCLC cells [29].…”
Section: Discussionmentioning
confidence: 99%
“…Although miRNAs play key roles during normal developmental processes, deregulation of miRNA expression has been noted in several human cancers in which miRNAs have been shown to have both oncogenic and tumor suppressor functions . miR‐7‐5p was downregulated and functions as a potent tumor suppressor in multiple cancer types, including breast cancer . In prior research, miR‐7 expression was negatively correlated with stage, grade and survival for breast cancer patients, and overexpression of miR‐7 inhibited the proliferation, invasion, and migration of breast cancer cells …”
Section: Introductionmentioning
confidence: 98%
“…The miRNAs are involved in various cellular processes of cancer development, including cell proliferation, differentiation, migration and invasion [1215]. Emerging evidence has identified that the deregulation of miRNAs is related to initiation of various cancers, such as bladder cancer, gastric cancer, lung cancer, and breast cancer [16, 17].…”
Section: Introductionmentioning
confidence: 99%